THE IMPACT OF ONLINE GAME ADDICTION ON GEN Z AND EFFORTS TO OVERCOME IT IN ISLAMIC PERSPECTIVES - Fiqra Muhammad Nazib; Muhammad Lutfi Alfayumi; Sansan Nurjaman; Alam Supriatna; Irma Siti Maliya (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The impact of online game addiction on Generation Z, which is becoming increasingly concerning in today's digital era. This addiction not only has negative effects on individuals' mental health but also potentially lowers academic achievement and disrupts social relationships. This phenomenon has been globally recognized, with the World Health Organization (WHO) classifying Gaming Disorder as a serious mental health condition. In this context, this article explores solutions offered by the Islamic perspective, which emphasizes the importance of balance in life, self-control, and engagement in positive activities. Several practical steps proposed include implementing strong religious education, effective time management, and increasing awareness about the risks of game addiction through lectures and seminars. With an approach based on Islamic moral values, it is hoped that Generation Z can manage their time wisely, avoid the negative effects of online game addiction, and lead a more balanced and meaningful life. This approach also includes strengthening morality and developing responsibility, as well as encouraging positive activities that can replace excessive gaming time.